Big data and human biosensors – birthweight as a biomonitor for air pollution levels. A population based study using routine data. - Chris Dibben; Tom Clemens (International Journal of Population Data Science, 2018)
Introduction In the natural sciences biomonitors, (organisms, such as pine needles, shells, lichen, that can provide quantitative information on the quality of their past and present environments) have been developed for environmental measurement. In recent year’s physiologists have started to explore if human tissue could also be used.